Green concrete using stone chips as fine aggregate and preparation method thereof
By copolymerizing quaternary ammonium-type water reducer with epoxychlorohydrin-diethanolamine copolymer with dimethyl butynylphenol polyethylene glycol ether in concrete that fully utilizes stone chips as fine aggregates, it is compounded with potassium nitrate and diethylenetriamine pentamethylphosphonate, combined with polycarboxylic acid jellyfish liquor, polycarboxylic acid comprehensive mother liquor and polycarboxylic acid slump-protective mother liquor, the problem of insufficient fluidity, strength and slump-retaining performance of the stone chip concrete is achieved, and better engineering performance is achieved.
Patent Information
- Application Number
- CN202410633149.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-21
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-05-21
AI Technical Summary
The prior art is difficult to effectively improve the fluidity, strength and slump retention properties of concrete that fully utilizes stone chips as fine aggregates, especially due to the fluidity and strength problems caused by high stone powder content.
The epoxychlorohydrin-diethanolamine copolymer was used to copolymerize with dimethyl butyndicate and nonylphenol polyethylene glycol ether to prepare a quaternary ammonium salt water reducer, and compounded with potassium nitrate and diethylenetriamine pentamethylphosphonate pentasulfonate, combined with polycarboxylic acid jellyfish liquor, polycarboxylic acid comprehensive mother liquor and polycarboxylic acid slump-resistant mother liquor, used to prepare green concrete that fully utilizes stone chips as fine aggregates.
The fluidity, strength and collapse-retaining properties of concrete that fully utilizes stone chips as fine aggregates have been significantly improved, and the fluidity and strength problems caused by high stone powder content have been solved, and better engineering performance has been achieved.
Smart Images

Figure BDA0004850863690000061 
Figure BDA0004850863690000071 
Figure BDA0004850863690000072
Abstract
Description
Technical Field
[0001] The present application relates to the field of concrete, and in particular to a green concrete which fully utilizes stone chips as fine aggregate and a preparation method thereof. Background Art
[0002] With the rapid development of social economy, various types of construction projects are increasing day by day, and the demand for construction materials is also increasing day by day. At present, the sand used for construction is mainly river sand. Since river sand is a non-renewable resource and the resource distribution is uneven, coupled with years of excessive mining, river sand has long been in short supply, the price has continued to rise, and the quality has also declined significantly. A few years ago, the mud content of river sand purchased on the market was generally around 3%, but now it has risen to 5% or even higher, and excessive sand mining in the river has also had an adverse impact on the ecological environment.
[0003] In recent years, in order to cope with the contradiction between supply and demand of river sand, respond to the requirements of green engineering construction, and reduce construction costs, artificial sand is usually used instead of medium-coarse sand (river sand) in engineering projects, and granite chips are tried instead of medium-coarse sand (river sand) to prepare green concrete.
[0004] Since river sand is formed from sand-like particles of natural stone that is repeatedly impacted and rubbed during natural movement, river sand is used as fine aggregate in concrete, and the mixed slurry made from it has relatively excellent density and fluidity. Artificial sand is made by crushing rock raw materials into fine particles by machine, so there is usually a certain amount of stone powder (particles smaller than 0.075mm) in it. Since stone powder has a large specific surface area and strong water absorption, it will reduce the fluidity of concrete. Therefore, it is stipulated that the stone powder content in artificial sand shall not exceed 15%. Artificial sand within the above standards is used in concrete, and the addition of conventional polycarboxylic acid-based high-efficiency water reducers on the market can also make its concrete mixture have good fluidity, cohesion and water retention.
[0005] Stone chips are byproducts formed in the process of mechanical processing of crushed stones in quarries. According to the national standard GB / T14684-2022 "Sand for Construction", stone chips can be classified as artificial sand, which is a possible substitute for river sand. As a byproduct of stone processing, the material price of stone chips usually has a greater price advantage than river sand and machine-made sand. Therefore, using stone chips as fine aggregate for concrete can not only turn waste into treasure, meet the requirements of environmental protection and energy saving, but also further reduce the cost of concrete, and have high practicality and economy. However, through investigation and analysis of various stone chips, it was found that the stone powder content in 80% of the stone chips exceeded the requirement of "Sand for Construction" that the content of machine-made sand and stone powder should not exceed 10%, and the stone powder content of some stone chips exceeded 15%. Due to the large specific surface area and strong water absorption of stone powder particles, it is difficult to maintain good fluidity, cohesion and water retention of concrete mixtures using stone chips as fine aggregates using the current conventional polycarboxylic acid-based high-efficiency water reducer, which has a greater negative impact on the strength, fluidity and collapse retention of concrete. Summary of the invention
[0006] In order to make the concrete that fully utilizes stone chips as fine aggregate have better strength, fluidity and collapse resistance, the present application provides a green concrete that fully utilizes stone chips as fine aggregate and a preparation method thereof.
[0007] In the first aspect, the present application provides a green concrete that fully utilizes stone chips as fine aggregate and adopts the following technical solution:
[0008] A green concrete that fully utilizes stone chips as fine aggregate, comprising the following components and their weight parts: 75-80 parts of cement, 9-10 parts of fly ash, 215-220 parts of coarse aggregate, 155-165 parts of stone chips, 2-5 parts of universal water reducing agent and 40-55 parts of water;
[0009] The universal water reducer comprises the following components and their contents: 14-18% of polycarboxylic acid water reducing mother liquor, 11-15% of polycarboxylic acid comprehensive mother liquor, 3-5% of polycarboxylic acid slump retaining mother liquor, 3-4% of retarder, 0.15-0.2% of air entraining agent, 2-4% of thickener, 0.01-0.1% of viscosity modifier, and the balance is water;
[0010] The polycarboxylic acid water-reducing mother liquor comprises a quaternary ammonium salt water-reducing agent, potassium nitrate, pentasodium diethylenetriamine penta (methylenephosphonic acid) and water in a mass ratio of 1: (0.8-1.1): (4-6): (12-14); the quaternary ammonium salt water-reducing agent is obtained by polymerizing epichlorohydrin-diethanolamine copolymer, dimethyl butynedioate and nonylphenol polyglycol ether.
[0011] By adopting the above technical scheme, the epichlorohydrin-diethanolamine copolymer can play a flocculation role in the polymerization reaction system, dimethyl butynedioate and nonylphenol polyglycol ether are co-coagulated to obtain a polycarboxylic acid water reducer, and the epichlorohydrin-diethanolamine copolymer is copolymerized with dimethyl butynedioate and nonylphenol polyglycol ether at the same time. The epichlorohydrin-diethanolamine copolymer can aggregate dimethyl butynedioate and nonylphenol polyglycol ether in the reaction system by adsorption, bridging, etc., so as to promote the polymerization reaction and improve the polymerization stability of the copolymer. The water reducer obtained by the polymerization of epichlorohydrin-diethanolamine copolymer, dimethyl butynedioate and nonylphenol polyglycol ether has more ionic groups such as hydroxyl groups and carboxylic acid groups, which can be better directed to be adsorbed on cement particles, so that the surface of cement particles carries the same charge, forming an electrostatic repulsion effect, and promoting the mutual dispersion of cement particles. Moreover, since the epichlorohydrin molecule contains two active atoms, the adsorption effect between the epichlorohydrin molecule and the cement particles is stronger, which can enhance the directional adsorption degree between the quaternary ammonium salt water reducer molecule and the surface of the cement particles, make the surface of the cement particles carry the same charge more fully, further promote the mutual dispersion of the cement particles, and release part of the water wrapped in the cement and stone powder flocculation structure, thereby effectively increasing the fluidity of the concrete mixture that fully utilizes stone chips as fine aggregate.
[0012] Furthermore, the quaternary ammonium salt-type water reducer formed by polymerization of epichlorohydrin-diethanolamine copolymer, dimethyl butynedioate and nonylphenol polyglycol ether is compounded with potassium nitrate and pentasodium diethylenetriamine penta (methylenephosphonic acid), which can promote the release, reaction and evaporation of water in the concrete mixture. At the same time, when combined with a retarder, the evaporation of water can be controlled to improve the hydration and curing rate and effect of the concrete, avoid cracking of the concrete after curing, and effectively improve the strength and fluidity of the concrete that fully utilizes stone chips as fine aggregate.
[0013] At the same time, compounding polycarboxylic acid water-reducing mother liquor and polycarboxylic acid comprehensive mother liquor, polycarboxylic acid slump-preserving mother liquor, retarder, air entraining agent, thickener and viscosity modifier and adding them into concrete mixture can improve the fluidity, cohesiveness and water retention of concrete mixture, so that concrete which fully utilizes stone chips as fine aggregate can achieve better slump-preserving performance and mechanical properties.
[0014] Optionally, the preparation method of the quaternary ammonium salt water reducer comprises the following steps:
[0015] The epichlorohydrin-diethanolamine copolymer, nonylphenol polyglycol ether and water are heated while stirring until they are completely dissolved, an initiator is added, and then a 35-38% dimethyl butynedioate solution is added dropwise within 2-3 hours, the mixture is kept warm for 0.5-1 hour, cooled, and the pH is adjusted to 6-7 to obtain the quaternary ammonium salt type water reducer.
[0016] Optionally, the molar ratio of the epichlorohydrin-diethanolamine copolymer, nonylphenol polyglycol ether and dimethyl butynedioate is 1:(0.25-0.30):(0.1-0.2).
[0017] By adopting the above technical scheme, epichlorohydrin-diethanolamine copolymer, nonylphenol polyglycol ether and dimethyl butynedioate are polymerized according to the above molar ratio, the stability of the copolymer can be improved, and the obtained quaternary ammonium salt type water reducer can better improve the improvement effect on the fluidity of concrete that fully utilizes stone chips as fine aggregate.
[0018] Optionally, the polycarboxylic acid comprehensive mother solution is obtained by polymerization reaction of polyoxyalkyl methyl allyl ether, isooctyl 3-mercaptopropionate and acrylic acid in a molar ratio of 1:(0.4-0.6):(0.7-0.9).
[0019] By adopting the above technical scheme, the water-reducing polymer obtained after polymerization of polyoxyalkyl methyl allyl ether, isooctyl 3-mercaptopropionate and acrylic acid has high dispersibility, and the addition of isooctyl 3-mercaptopropionate in the above molar ratio can adjust the molecular weight of the obtained water-reducing polymer to obtain a small molecule admixture, and the above polycarboxylic acid comprehensive mother liquor and polycarboxylic acid water-reducing mother liquor are compounded for use, so that the water-reducing agent molecules formed by adsorption on the surface of cement particles can be arranged more closely, further enhancing the electrostatic repulsion between cement particles, so as to further improve the fluidity of concrete mixtures using stone chips as fine aggregates.
[0020] Optionally, the polycarboxylic acid collapse-retaining mother solution is a copolymer obtained by mixing polyethylene glycol 400 mono(meth)acrylate, polyethylene glycol 1000 mono(meth)acrylate, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid in a molar ratio of 1:(9-10):(0.5-0.7):(1.1-1.3) and polymerizing the mixture.
[0021] By adopting the above technical scheme, two macromonomers, polyethylene glycol 400 mono(meth)acrylate and polyethylene glycol 1000 mono(meth)acrylate, are used to carry out multi-polymerization with 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid to obtain a polymer. The chain lengths of the two macromonomers can enable the obtained polymer to provide more and greater steric hindrance effects between cement particles, so as to better hinder the coagulation between cement particles, so as to significantly improve the slump of concrete with stone chips as fine aggregate, and enable the concrete mixture to have better slump retention performance.
[0022] Optionally, the retarder is at least one of citric acid, gluconic acid and salicylic acid.
[0023] By adopting the above technical solution, the above retarder is combined with potassium nitrate and pentasodium diethylenetriamine penta (methylene phosphonate) in the polycarboxylic acid water-reducing mother liquor, so as to better control the hydration rate of concrete and the evaporation amount of water, so as to improve the concrete curing efficiency while reducing the possibility of drying, shrinkage and cracking caused by the hydration and hardening time of concrete that fully utilizes stone chips as fine aggregate being too fast.
[0024] Optionally, the air entraining agent is at least one of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate.
[0025] By adopting the above technical scheme, the above air-entraining agent is compounded with polycarboxylic acid water-reducing mother liquor and polycarboxylic acid comprehensive mother liquor for use as a universal water-reducing agent, which can form a large number of tiny closed spherical bubbles in the concrete mixture. These bubbles work synergistically with the water-reducing agent molecules adsorbed on the surface of cement particles, and can better improve the fluidity of the concrete mixture that fully utilizes stone chips as fine aggregate.
[0026] Optionally, the thickener is at least one of polyacrylamide, polystyrene and polyvinyl alcohol.
[0027] By adopting the above technical solution, the above thickener and polycarboxylic acid slump-retaining mother solution are compounded and used as a universal water reducer, so that the concrete that fully utilizes stone chips as fine aggregate can maintain better cohesiveness and water retention.
[0028] Optionally, the viscosity modifier is at least one of acrylate and silicone rubber.
[0029] By adopting the above technical solution, the viscosity modifier is compounded with a thickener and a polycarboxylic acid collapse-retaining mother solution, so that the cohesiveness and water retention of the concrete can be further improved.
[0030] In the second aspect, the present application provides a method for preparing green concrete that fully utilizes stone chips as fine aggregate, which adopts the following technical solution:
[0031] A method for preparing green concrete using stone chips as fine aggregate comprises the following steps:
[0032] First, the polycarboxylic acid water-reducing mother solution, polycarboxylic acid comprehensive mother solution, polycarboxylic acid collapse-preserving mother solution, retarder, air entraining agent, thickener, viscosity modifier and water in the above-mentioned amounts are stirred and mixed in sequence at room temperature to obtain a universal water-reducing agent;
[0033] The above-mentioned weight portions of cement, fly ash, coarse aggregate, stone chips, universal water reducer and water are added in sequence for stirring. The water is added in three times during the stirring process to obtain a green concrete mixture.
[0034] In summary, the present application includes at least one of the following beneficial technical effects:
[0035] 1. The epichlorohydrin-diethanolamine copolymer is copolymerized with dimethyl butynedioate and nonylphenol polyglycol ether, and dimethyl butynedioate and nonylphenol polyglycol ether in the reaction system can be aggregated by adsorption, bridging and the like, so as to promote the polymerization reaction and improve the polymerization stability of the copolymer; and, since the epichlorohydrin molecule contains two active atoms, the adsorption effect between the epichlorohydrin molecule and the cement particles is stronger, and the directional adsorption degree between the quaternary ammonium salt type water reducer molecule and the surface of the cement particles can be improved, so that the surface of the cement particles is more fully charged with the same charge, forming an electrostatic repulsion effect, and promoting the mutual dispersion of the cement particles, and releasing part of the water wrapped in the cement and stone powder flocculation structure, thereby effectively increasing the fluidity of the concrete mixture that fully utilizes stone chips as fine aggregate;
[0036] 2. Compounding the polymer formed by epichlorohydrin-diethanolamine copolymer, dimethyl butynedioate and nonylphenol polyglycol ether with potassium nitrate and pentasodium diethylenetriamine penta(methylenephosphonic acid) can promote the release, reaction and evaporation of water in the concrete mixture. At the same time, when combined with a retarder, the evaporation of water can be well controlled to improve the curing rate and effect of the concrete, and avoid cracking of the concrete after curing, thereby effectively improving the strength and fluidity of the concrete that fully utilizes stone chips as fine aggregate;
[0037] 3. The water-reducing polymer obtained by polymerization of polyoxyalkyl methyl allyl ether, isooctyl 3-mercaptopropionate and acrylic acid has high dispersibility, and the addition of isooctyl 3-mercaptopropionate in the above molar ratio can adjust the molecular weight of the obtained water-reducing polymer to obtain a small molecule admixture. The above polycarboxylic acid comprehensive mother liquor and polycarboxylic acid water-reducing mother liquor are compounded for use, and the water-reducing agent molecules formed by adsorption on the surface of cement particles can be arranged more closely, further enhancing the electrostatic repulsion between cement particles, so as to further improve the fluidity of concrete mixtures with stone chips as fine aggregate. DETAILED DESCRIPTION
[0038] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0039] 1. Implementation
[0040] Embodiment 1:
[0041] A green concrete using stone chips as fine aggregate comprises the following components and their weight parts (calculated based on 1000 kg as the total):
[0042] 75 parts of cement, 9 parts of fly ash, 215 parts of coarse aggregate, 155 parts of stone chips, 2 parts of universal water reducer and 40 parts of water;
[0043] The cement is of strength grade 52.5R; the coarse aggregate is granite crushed stone with a particle size of 5-6 mm; the fineness modulus of the stone chips is 2.48, the stone powder content is 16.4%, and the original parent material of the stone chips is granite;
[0044] Among them, the universal water reducer includes the following components and their contents: 16% polycarboxylic acid water-reducing mother liquor, 13% polycarboxylic acid comprehensive mother liquor, 4% polycarboxylic acid slump-retaining mother liquor, 3.5% retarder, 0.18% air entraining agent, 3% thickener, 0.05% viscosity modifier, and the balance is water;
[0045] The retarder is citric acid, the air entraining agent is sodium dodecylbenzene sulfonate, the thickener is polyacrylamide (molecular weight is 2 million), and the viscosity modifier is acrylate; wherein the polycarboxylic acid water-reducing mother liquor comprises a quaternary ammonium salt water-reducing agent, potassium nitrate, diethylenetriamine pentasodium methylenephosphonate and water in a mass ratio of 1:0.9:5:13;
[0046] The preparation method of quaternary ammonium salt water reducer comprises the following steps:
[0047] Add epichlorohydrin-diethanolamine copolymer, nonylphenol polyglycol ether and water into a reaction container, stir and heat until completely dissolved, add ammonium persulfate, and then dropwise add 37% dimethyl butynedioate solution within 2.5 hours, keep warm for 1 hour to carry out polymerization reaction, cool, adjust the pH to 7, and obtain a quaternary ammonium salt type water reducer; wherein the molar ratio of epichlorohydrin-diethanolamine copolymer, nonylphenol polyglycol ether and dimethyl butynedioate is 1:0.28:0.15.
[0048] The method for preparing the polycarboxylic acid comprehensive mother solution comprises the following steps:
[0049] The reaction vessel was placed in a constant temperature water bath at 70°C, a certain amount of distilled water was added to the reaction vessel, and the mixture was stirred for a period of time. Polyoxyalkyl methyl allyl ether (purchased from Hangzhou Danwei Technology Co., Ltd.), 3-mercaptopropionate and acrylic acid were added in sequence, and the mixture was stirred for 10 minutes. Ammonium persulfate was added, and the temperature was kept constant. After the polymerization reaction lasted for 3 hours, the temperature was lowered to 35°C, and the pH value of the product was adjusted to 8 with NaOH solution, and the reaction was continued for 1 hour. Finally, a certain amount of acrylic acid was added to adjust the pH value to 6-7 to obtain a comprehensive polycarboxylic acid mother liquor. The molar ratio of polyoxyalkyl methyl allyl ether, 3-mercaptopropionate and acrylic acid was 1:0.5:0.8.
[0050] Wherein, the preparation method of polycarboxylic acid collapse-preserving mother solution comprises the following steps:
[0051] Mixing polyethylene glycol 400 mono(meth)acrylate, polyethylene glycol 1000 mono(meth)acrylate, 2-acrylamide-2-methylpropanesulfonic acid, and acrylic acid at a molar ratio of 1:9.5:0.6:1.2 to obtain a monomer mixed solution;
[0052] A small amount of deionized water and ethanol initial solvents were added, and when heated to 70°C, the monomer mixed solution and ammonium persulfate were added dropwise under constant temperature and continuous stirring to carry out polymerization reaction. After 4 hours, the mixture was cooled and neutralized with an organic amine solution to a pH value of 7. The solid phase mass of the reaction system solution was adjusted to be within the range of 25% to obtain a polycarboxylic acid collapse-resistant mother solution.
[0053] The preparation method of the universal water reducing agent comprises the following steps:
[0054] According to the above content, weigh and add polycarboxylic acid water-reducing mother solution, polycarboxylic acid comprehensive mother solution, polycarboxylic acid collapse-preserving mother solution, citric acid, sodium dodecylbenzene sulfonate, polyacrylamide, acrylate and water in sequence, stir and mix evenly at room temperature (20-25° C.) to obtain a universal water reducer.
[0055] The method for preparing green concrete using stone chips as fine aggregate comprises the following steps:
[0056] Taking 1000 kg as the total, the above weight portions of cement, fly ash, coarse aggregate, stone chips, general water reducer and water are added and stirred. The water is added in 3 times during the stirring process, and one-third of water is added each time. After stirring evenly, a green concrete mixture is obtained. After solidification and curing, green concrete which fully utilizes stone chips as fine aggregate is obtained.
[0057] Embodiment 2-3:
[0058] A green concrete that fully utilizes stone chips as fine aggregate, the differences from Example 1 are shown in Table 1.
[0059] Table 1:
[0060]
[0061]
[0062] Embodiment 4-5:
[0063] A green concrete that fully utilizes stone chips as fine aggregate, the differences from Example 2 are shown in Table 2.
[0064] Table 2:
[0065]
[0066] Embodiment 6:
[0067] A green concrete that fully utilizes stone chips as fine aggregate is different from Example 2 in that the mass ratio of quaternary ammonium salt water reducer, potassium nitrate, diethylenetriamine pentasodium methylenephosphonate and water in the polycarboxylic acid water-reducing mother liquor is 1:0.8:4:12.
[0068] Embodiment 7:
[0069] A green concrete that fully utilizes stone chips as fine aggregate is different from Example 2 in that: in the polycarboxylic acid water-reducing mother liquor, the mass ratio of quaternary ammonium salt water reducer, potassium nitrate, diethylenetriamine pentasodium methylenephosphonate and water is 1:1.1:6:14.
[0070] Embodiment 8:
[0071] A green concrete that fully utilizes stone chips as fine aggregate is different from Example 2 in that: during the preparation of the quaternary ammonium salt water reducer, the molar ratio of epichlorohydrin-diethanolamine copolymer, nonylphenol polyglycol ether and dimethyl butynedioate is 1:0.25:0.1.
[0072] Embodiment 9:
[0073] A green concrete that fully utilizes stone chips as fine aggregate is different from Example 2 in that: during the preparation of the quaternary ammonium salt water reducer, the molar ratio of epichlorohydrin-diethanolamine copolymer, nonylphenol polyglycol ether and dimethyl butynedioate is 1:0.30:0.2.
[0074] Embodiment 10:
[0075] A green concrete that fully utilizes stone chips as fine aggregate is different from Example 2 in that: during the preparation of the polycarboxylic acid comprehensive mother solution, the molar ratio of polyoxyalkyl methyl allyl ether, 3-mercaptopropionic acid isooctyl ester and acrylic acid is 1:0.4:0.7.
[0076] Embodiment 11:
[0077] A green concrete that fully utilizes stone chips as fine aggregate is different from Example 2 in that: during the preparation of the polycarboxylic acid comprehensive mother solution, the molar ratio of polyoxyalkyl methyl allyl ether, 3-mercaptopropionate and acrylic acid is 1:0.6:0.9.
[0078] Embodiment 12:
[0079] A green concrete that fully utilizes stone chips as fine aggregate is different from Example 2 in that: in the preparation process of the polycarboxylic acid collapse-retaining mother solution, the molar ratio of polyethylene glycol 400 mono(meth)acrylate, polyethylene glycol 1000 mono(meth)acrylate, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid is 1:9:0.5:1.1.
[0080] Embodiment 13:
[0081] A green concrete that fully utilizes stone chips as fine aggregate is different from Example 2 in that: in the preparation process of the polycarboxylic acid collapse-retaining mother solution, the molar ratio of polyethylene glycol 400 mono(meth)acrylate, polyethylene glycol 1000 mono(meth)acrylate, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid is 1:10:0.7:1.3.
[0082] 2. Comparison
[0083] Comparative Example 1:
[0084] The difference from Example 2 is that an equal amount of the polycarboxylic acid comprehensive mother liquor is replaced by the polycarboxylic acid water-reduced mother liquor.
[0085] Comparative Example 2:
[0086] The difference from Example 2 is that an equal amount of the polycarboxylic acid collapse-retaining mother liquor is replaced by a polycarboxylic acid water-reducing mother liquor.
[0087] Comparative Example 3:
[0088] The difference from Example 2 is that an equal amount of the retarder is replaced by a polycarboxylic acid water-reducing concentrate.
[0089] Comparative Example 4:
[0090] The difference from Example 2 is that the quaternary ammonium salt water reducer is replaced by potassium nitrate in equal amount.
[0091] Comparative Example 5:
[0092] The difference from Example 2 is that an equal amount of diethylenetriamine pentasodium methylenephosphonate is replaced by a quaternary ammonium salt type water reducer.
[0093] 3. Performance test
[0094] 1) Dispersion performance test:
[0095] According to GB / T 8077-2012 (Test method for homogeneity of concrete admixtures), the fluidity of the green concrete mixtures of Examples 1-13 and Comparative Examples 1-5 was measured, and the measurement results are shown in Table 3;
[0096] 2) Collapse resistance test:
[0097] According to GB / T 8076-2008 (Concrete Admixtures), the slump of the green concrete mixtures of Examples 1-13 and Comparative Examples 1-5 at 30min and 60min was measured respectively, and the measurement results are shown in Table 3;
[0098] 3) Compressive strength test:
[0099] The green concrete specimens of Examples 1-13 and Comparative Examples 1-5 after the water permeability coefficient was measured were first drained of the water inside the specimens and the water on the surface of the specimens was wiped dry, and then the 28d compressive strength of the concrete test blocks of Examples 1-13 and Comparative Examples 1-5 was tested and calculated according to GB / T 50081. The test results are shown in Table 3.
[0100] Table 3:
[0101]
[0102] Combining Examples 1-3 and Table 3, it can be seen that the concrete components and their weight portions in Examples 1-3 are all different. It can be seen from Table 3 that the fluidity of Examples 1-3 is all >210 mm, the slump at 30 min and 60 min is all >210 mm, and the compressive strength is all >45 MPa, and the fluidity, collapse protection performance and strength of Example 2 are all better than those of Example 1 and Example 3. It can be seen from the above that compounding the concrete components and their weight portions within the scope of this application can make the fluidity, collapse protection performance and strength of the fine aggregate concrete fully utilizing stone chips better, and compounding the components according to the weight portions of Example 2 can obtain relatively better fluidity, collapse protection performance and strength of the obtained concrete.
[0103] Combining Example 2, Examples 4-5 and Table 3, it can be seen that the contents of each component in the universal water reducer of Example 4-5 are different from those in Example 2. It can be seen from Table 3 that the fluidity of Examples 4-5 is all >210 mm, the slump at 30 min and 60 min is all >210 mm, and the compressive strength is all >45 MPa, but the fluidity, slump retention performance and strength of Example 2 are better than those of Examples 4-5.
[0104] In addition, in comparison examples 1-3, in comparison example 1, an equal amount of polycarboxylic acid comprehensive mother liquor is replaced with a polycarboxylic acid water-reducing mother liquor, in comparison example 2, an equal amount of polycarboxylic acid slump-preserving mother liquor is replaced with a polycarboxylic acid water-reducing mother liquor, and in comparison example 3, an equal amount of retarder is replaced with a polycarboxylic acid water-reducing mother liquor. As can be seen from Table 3, the fluidity, slump at 30min and 60min, and compressive strength of comparison examples 1-3 are much lower than those of example 2.
[0105] From the above, it can be concluded that within the scope of the present application, compounding the components such as polycarboxylic acid water-reducing mother liquor, polycarboxylic acid comprehensive mother liquor, polycarboxylic acid slump-retaining mother liquor and retarder in the universal water-reducing agent can significantly improve the fluidity, slump-retaining performance and strength of the fine aggregate concrete that fully utilizes stone chips; and compounding the components in the universal water-reducing agent according to the contents in Example 2, the fluidity, slump-retaining performance and strength of the obtained concrete are relatively better.
[0106] Combining Example 2, Example 6-7 and Table 3, it can be seen that in the polycarboxylate water-reducing concentrate of Example 6-7, the mass ratios of quaternary ammonium salt water-reducing agent, potassium nitrate, diethylenetriamine pentasodium methylenephosphonate and water are different from those in Example 2. As can be seen from Table 3, the fluidity of Example 6-7 is all >210 mm, the slump at 30 min and 60 min is all >210 mm, and the compressive strength is all >45 MPa, but the fluidity, slump retention performance and strength of Example 2 are better than those of Example 6-7.
[0107] In addition, in Comparative Example 4-5, the quaternary ammonium salt water reducer is replaced by potassium nitrate in an equal amount in Comparative Example 4, and the diethylene triamine pentasodium methylene phosphonate is replaced by a quaternary ammonium salt water reducer in an equal amount in Comparative Example 5. As can be seen from Table 3, the fluidity, slump at 30min and 60min, and compressive strength of Comparative Example 4-5 are all much lower than those of Example 2.
[0108] From the above, it can be concluded that within the scope of the present application, compounding a quaternary ammonium salt water reducer, potassium nitrate and pentasodium diethylenetriamine penta(methylenephosphonic acid) to obtain a polycarboxylic acid water-reducing concentrate can significantly improve the fluidity, slump retention and strength of concrete with all stone chips as fine aggregate; and when the mass ratio of the quaternary ammonium salt water reducer, potassium nitrate, pentasodium diethylenetriamine penta(methylenephosphonic acid) and water is 1:0.9:5:13, the fluidity, slump retention and strength of the obtained concrete are relatively better.
[0109] Combining Example 2, Examples 8-9 and Table 3, it can be seen that the molar ratios of epichlorohydrin-diethanolamine copolymer, nonylphenol polyglycol ether and dimethyl butynedioate in Examples 8-9 are all different from those in Example 2. As can be seen from Table 3, the fluidity of Examples 8-9 is all >210 mm, the slump at 30 min and 60 min is all >210 mm, and the compressive strength is all >45 MPa, but the fluidity, slump retention performance and strength of Example 2 are all better than those of Examples 8-9.
[0110] From the above, it can be concluded that the quaternary ammonium salt water reducer obtained by polymerizing epichlorohydrin-diethanolamine copolymer, nonylphenol polyglycol ether and dimethyl butynedioate is mixed with potassium nitrate, diethylenetriamine pentasodium methylenephosphonate and water to obtain a polycarboxylic acid water-reducing concentrate, which can significantly improve the fluidity, slump retention and strength of concrete with all stone chips as fine aggregate; and when the molar ratio of epichlorohydrin-diethanolamine copolymer, nonylphenol polyglycol ether and dimethyl butynedioate is 1:0.28:0.15, the fluidity, slump retention and strength of the obtained concrete are relatively better.
[0111] Combining Example 2, Example 10-11 and Table 3, it can be seen that in the preparation process of the polycarboxylic acid comprehensive mother solution of Example 10-11, the molar ratios of polyoxyalkyl methyl allyl ether, 3-mercaptopropionate isooctyl ester and acrylic acid are all different from those of Example 2. From Table 3, it can be seen that the fluidity of Examples 10-11 is all >210mm, the slump at 30min and 60min is all >210mm, and the compressive strength is all >45MPa. It can be obtained from the above that within the scope of this application, polyoxyalkyl methyl allyl ether, 3-mercaptopropionate isooctyl ester and acrylic acid are compounded to obtain a polycarboxylic acid comprehensive mother solution, which can significantly improve the fluidity, slump retention and strength of fine aggregate concrete that fully utilizes stone chips.
[0112] In combination with Example 2, Example 12-13 and Table 3, it can be seen that in the preparation process of the polycarboxylic acid slump-retaining mother solution of Example 12-13, the molar ratios of polyethylene glycol 400 mono(meth)acrylate, polyethylene glycol 1000 mono(meth)acrylate, 2-acrylamide-2-methylpropane sulfonic acid and acrylic acid are all different from those of Example 2. As can be seen from Table 3, the fluidity of Examples 12-13 is all >210mm, the slump of 30min and 60min is all >210mm, and the compressive strength is all >45MPa. As can be seen from the above, within the scope of this application, polyethylene glycol 400 mono(meth)acrylate, polyethylene glycol 1000 mono(meth)acrylate, 2-acrylamide-2-methylpropane sulfonic acid and acrylic acid are compounded to obtain a polycarboxylic acid slump-retaining mother solution, which can significantly improve the fluidity, slump-retaining performance and strength of fine aggregate concrete that fully utilizes stone chips.
[0113] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A green concrete that fully utilizes stone chips as fine aggregate, characterized in that: It includes the following components and their weight parts: 75-80 parts of cement, 9-10 parts of fly ash, 215-220 parts of coarse aggregate, 155-165 parts of stone chips, 2-5 parts of universal water reducing agent and 40-55 parts of water; The universal water reducer comprises the following components and their contents: 14-18% polycarboxylic acid water reducing mother liquor, 11-15% polycarboxylic acid comprehensive mother liquor, 3-5% polycarboxylic acid slump retaining mother liquor, 3-4% retarder, 0.15-0.2% air entraining agent, 2-4% thickener, 0.01-0.1% viscosity modifier, and the balance is water; The polycarboxylic acid water-reducing mother liquor comprises a quaternary ammonium salt water-reducing agent, potassium nitrate, diethylenetriamine pentasodium methylenephosphonate and water in a mass ratio of 1: (0.8-1.1): (4-6): (12-14); the quaternary ammonium salt water-reducing agent is obtained by polymerization of epichlorohydrin-diethanolamine copolymer, dimethyl butynedioate and nonylphenol polyglycol ether; The polycarboxylic acid comprehensive mother solution is obtained by polymerization reaction of polyoxyalkyl methyl allyl ether, 3-mercaptopropionic acid isooctyl ester and acrylic acid in a molar ratio of 1: (0.4-0.6): (0.7-0.9); The polycarboxylic acid collapse-preserving mother solution is prepared by mixing polyethylene glycol 400 mono(meth)acrylate, polyethylene glycol 1000 mono(meth)acrylate, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid in a molar ratio of 1:(9-10):(0.5-0.7):(1.1-1.3) to obtain a copolymer.
2. The green concrete using stone chips as fine aggregate according to claim 1, characterized in that: The preparation method of the quaternary ammonium salt water reducer comprises the following steps: The epichlorohydrin-diethanolamine copolymer, nonylphenol polyglycol ether and water are heated while stirring until they are completely dissolved, an initiator is added, and then a 35-38% dimethyl butynedioate solution is added dropwise within 2-3 hours, the mixture is kept warm for 0.5-1 hour, cooled, and the pH is adjusted to 6-7 to obtain the quaternary ammonium salt type water reducer.
3. The green concrete using stone chips as fine aggregate according to claim 2 is characterized in that: The molar ratio of the epichlorohydrin-diethanolamine copolymer, nonylphenol polyglycol ether and dimethyl butynedioate is 1:(0.25-0.30):(0.1-0.2).
4. The green concrete using stone chips as fine aggregate according to claim 1, characterized in that: The retarder is at least one of citric acid, gluconic acid and salicylic acid.
5. The green concrete using stone chips as fine aggregate according to claim 1, characterized in that: The air entraining agent is at least one of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate.
6. The green concrete using stone chips as fine aggregate according to claim 5, characterized in that: The thickener is at least one of polyacrylamide, polystyrene and polyvinyl alcohol.
7. The green concrete using stone chips as fine aggregate according to claim 6, characterized in that: The viscosity modifier is at least one of acrylate and silicone rubber.
8. A method for preparing green concrete using stone chips as fine aggregate as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: First, the polycarboxylic acid water-reducing mother solution, polycarboxylic acid comprehensive mother solution, polycarboxylic acid collapse-preserving mother solution, retarder, air entraining agent, thickener, viscosity modifier and water in the above-mentioned amounts are stirred and mixed in sequence at room temperature to obtain a universal water-reducing agent; The above-mentioned weight portions of cement, fly ash, coarse aggregate, stone chips, universal water reducer and water are added in sequence for stirring. The water is added in three times during the stirring process to obtain a green concrete mixture.
Citation Information
Patent Citations
Damped water reducing agent and preparation method for concrete
CN102775088A
Cement-based polycarboxylate superplasticizer mother liquor with ultralong-acting slump loss resistance and application thereof
CN110938176A